Caracterização do teste de escolha alimentar e desempenho zootécnico da tilápia-do-Nilo em dietas com adição de prebiótico e probiótico - Rezende, Silvana Barbosa (2019)
The objective of this study was to evaluate the predilection of Nile tilapia for a diet containing probiotic or prebiotic addition and to verify the effects of the additives in the choice of food, zootechnical performance, hematology and histology of the liver, intestine and muscle. The behavioral test of food choice used three diets (probiotic, prebiotic and control) consisting of one fish per aquarium totalizing 10 experimental units and observations in two shifts (morning and afternoon) for 56 days. At the same time, the test was used with three diets and four replicates, one fish per aquarium totalizing 12 experimental units to evaluate the zootechnical performance, hematology and histology. The mean values of the frequency of visits to the feeder and the quantity of pellets ingested by tilapia fed with the probiotic and prebiotic diets were lower (P <0.05) than the fish submitted to the control diet. The quantity of pellets ejected and mean tilapia feed time did not show significant differences, independently of the evaluated turn (P>0.05). The use of the additives did not show differences (P>0.05) in the zootechnical performance, number of erythrocytes and neutrophils, number of villi, intestinal villus height, intestinal length and intestinal weight of juvenile Nile tilapia among the three diets. The quantity of leukocytes, lymphocytes, and monocytes in fish fed with control diet were higher than those found in fish fed probiotic and prebiotic diets (P<0.05). The mean value of the hepatocyte area of the tilapia fed with probiotic diet was higher than that found in the prebiotic and control diets, while the highest values of fiber diameter and diameter class (> 40 μm) were observed in fish submitted to a prebiotic diet. The addition of prebiotic or probiotic to the commercial diet, under the conditions of the food choice test for juveniles of Nile tilapia, influences the frequency of visit to the feeder and quantity of ingested pellets, independently of the evaluated turn. The behavioral responses of dietary choice of the probiotic diet increases the area of the hepatocytes while the prebiotic diet promotes the increase of the diameter of the muscular fibers of the tilapia.